Exploring degree-seeking international student satisfaction through the example of a Hungarian university - Szabó Bálint; Paulics Lilla; Kéri Anita (2024)
International student satisfaction has become a widely studied topic with the emergence of English-language study programs in higher education institutions (HEIs). Numerous studies arose in connection with understanding what factors influence international student satisfaction, determining service elements as crucial indicators of student satisfaction. There is limited research on understanding international student satisfaction in Hungary, explicitly focusing on degree-seeking mobility. Therefore, the current study analyses international students' satisfaction through the example of a Hungarian university to uncover the factors affecting satisfaction and to determine points for improvement of unsatisfied needs. Based on the questionnaire findings, an importance–satisfaction analysis (ISA) was conducted to depict international students' pain points visually. The focus group discussion and the affinity diagrams revealed that international students need more free-time activities and opportunities to connect outside the university. In addition, usability testing highlighted crucial missing information from the university mentor organisation webpage, while the results of the online questionnaire showed that there is an urgent need to develop university services. Besides determining points for improvement, this study provides insights into utilising a comprehensive, novel methodology in researching degree-seeking mobile students in Hungary.
Keywords: Oktatástudomány